PENGEMBANGAN BAHAN AJAR KEWIRAUSAHAAN BERBASIS EKONOMI KREATIF - Rosidhah, Eny; Forijati, Rr (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
This study aims to determine the development of creative economy-based entrepreneurship teaching materials in class X SMK which teachers in the field of entrepreneurship can use as a reference and benchmark in the learning process for students which can later spur student entrepreneurship based on economic development. This study was designed with an R&D model. The model referred to as a Research and Development approach is research that develops creative economy-based entrepreneurship teaching materials for class X students. Subjects related to this research are class X Marketing 1 or control class and class X Marketing. 2 or experimental class in the 2019/2020 school year. The results showed that after testing using the SPSS 16 for windows program, the mean results of the pre-test and post-test for the experimental class were 46.75 and 67.10. Meanwhile, the mean for the control class was 39.76 and 55.62, so that the N-gain score for the experimental class was 20.35 and the N-gain score for the control class was 15.86. From these results it can be concluded that the experimental class learning outcomes have the highest average value when compared to the control class learning outcomes.